Frequency Reconfigurable Slotted Split-Ring Antenna - Raval, Falguni; Patel, Tulsi; Upadhaya, Trushit (International Journal of Sensors Wireless Communications and Control, 2020)
Background & Objective: Partially grounded frequency reconfigurable antenna is discussed in this paper. Antenna frequency cover is 4.2 GHz to 7 GHz and it has reconfigurable notchband near 5 GHz frequency. Frequency rejection is achieved by using circular split-ring slots in radiating element. The antenna can be reconfigured at 5.1 GHz, 5.4 GHz and 5.9 GHz by creating more slots in outer most split-ring. Designed antennas are printed on FR-4, low-cost substrate having relative permittivity of 4.4 and thickness of 1.6 mm. Results & Conclusion: Simulation of antennas is carried out using High Frequency Structure Simulator (HFSS) software. Designed antenna has omni directional radiation pattern. The prototype antennas are fabricated and tested using network analyzer. Good matching is observed between simulated and measured results.
Keywords: patch antenna